2015
DOI: 10.5717/jenb.2015.19.2.73
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regular Taekwondo exercise on Brain-derived neurotrophic factor and Stroop test in undergraduate student

Abstract: Young-Il Kim. The effect of Taekwondo Exercise on Brain-derived neurotrophic factor and Stroop test in undergraduate students. JENB., Vol. 19, No. 2, pp.73-79, 2015 [Purpose] The purpose of this study was to investigate the effect of Taekwondo exercise on Brain-derived neurotrophic factor and the Stroop test in undergraduate students.[Methods] Fourteen male subjects participated in this study. They were separated into a Control group (N = 7) and an Exercise group (N = 7). Subjects participated in Taekwondo ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
1
Order By: Relevance
“…The result showed that the TKD group achieved significantly higher Color-Word scores after the 16-week TKD training, suggesting that TKD training may be effective in improving cognitive function. This supports the findings of preceding research that reported significant increase in Stroop Color and Word Test scores following regular TKD training 12 ) . The Stroop Color and Word Test reflects cognitive function 9 ) .…”
Section: Discussionsupporting
confidence: 92%
“…The result showed that the TKD group achieved significantly higher Color-Word scores after the 16-week TKD training, suggesting that TKD training may be effective in improving cognitive function. This supports the findings of preceding research that reported significant increase in Stroop Color and Word Test scores following regular TKD training 12 ) . The Stroop Color and Word Test reflects cognitive function 9 ) .…”
Section: Discussionsupporting
confidence: 92%
“…For example, in the study conducted by Nikolaidis et al (8), the body fat percentage of female taekwondo athletes aged between 18 and 33 years, was reported 19%, or in another study done by Heller et al (12) on the athletes with black belts, it was reported 15%. Body fat percentage of female taekwondo athletes in the national team was reported 11.2% in Turkey ( 19) and 15.4% in Kazakhstan (20). Our findings were even higher than what was reported as the mean body fat percentage of the national taekwondo team athletes of Iran in 2006 (equal to 7%), despite the same measurement method (i.e., BIA) being applied to determine body fat percentage (9).…”
Section: Discussioncontrasting
confidence: 59%